Hundens kommunikationssignaler - Johansson, Philippa (2009)
This literature study summarizes the signals dogs use in intraspecific communication. The purpose is to clarify the way dogs communicate so that situations where their intentions are misjudged can be avoided. The signals are divided into olfactory, visual, auditory and tactile and every section starts with a short anatomic and physiologic description of the sense organ that is used to register the current signal type. The interspecific communication between dog and human regarding its development and function is brought up. To end with suggestions are given of how veterinary technicians in clinics can make use of knowledge about the way dogs communicate.